Religious Narratives and Diversity on Social Media: Analyzing the Digital Role in Strengthening Pluralism - Al Ayubbi, Syaefuddin Ahrom (Saneskara: Journal of Social Studies, 2025)
The rapid development of social media has significantly altered the way society engages with religious narratives, influencing perceptions of pluralism and moderate Islam. This study aims to examine the role of social media in shaping diversity narratives, with a particular focus on the Twitter account @AlissaWahid. Employing a content analysis approach, this research evaluates the messages disseminated through this account’s posts and their impact on public discourse regarding religious tolerance. The findings indicate that social media serves as an influential platform for fostering inclusivity, spreading messages of religious moderation, and countering radical narratives. Through the strategic use of inclusive language, visual content, and interactive engagement, the dissemination of diversity narratives becomes more effective and accessible to digital audiences. Furthermore, this study highlights the necessity of active participation from religious leaders, scholars, and civil society organizations to reinforce moderate Islamic discourse in online spaces. Strengthening these collaborative efforts is crucial to ensuring that social media continues to function as a medium for promoting harmony, pluralism, and religious coexistence in Indonesia.